(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this study, a microcontroller-based temperature sensing and recording system for application in healthcare was developed. One of the characteristics of this system is its ability to continually monitor a patient’s temperature while displaying the instantaneous result on a Liquid Crystal Display (LCD) monitor. The research’s technique was in The Electrically Erasable Programmable Read-Only Memory (EEPROM) device, which is part of the system and may be connected to a computer over USB, records the temperature observed every 10 minutes. In conclusion, an ATmega16 AVR serves as the brain that directs and coordinates all of the operations of the many modules. It permitted a doctor to take care of other things while keeping an eye on his patient’s condition. The temperature tracking system was used to inform some additional questions that were sent to the 100 hospital patients who were online. The responses were then reviewed. This study is being utilised to create new technologies, as well as to upgrade the staff and infrastructure of the hospital.